Separators in Orthodontics: A Review - Tarvade Daokar, Suchita (Orthodontic Journal of Nepal, 2016)
Placement of bands on the posterior teeth are preferred to bonding due to heavy masticatory forces. Placement of bands needs interdental separation of 0.2 mm, which requires prior placement of separators for couple of days. Various types of separators are commercially available in the market, with their own advantages and disadvantages. A scientific review of this most useful armamentarium in orthodontics was lacking and therefore a search was undertaken to gather information on separators. This article deals with various aspects of separators in detail. Orthodontic Journal of Nepal, Vol. 6 No. 1, June 2016, pp.37-40